MOVE On Up That Beanstalk, Jack! : The Fairy-Tale Physics of Forces and Motion - Troupe, Thomas Kingsley (PICTURE WINDOW BOOKS, 2019)
"When times are tough, you pull yourself up and push yourself to the top ... of a beanstalk ... where you might get schooled in forces and motion by a STEM-loving giant named Dennis. At least that's what happens to Jack in this delicious twist on a classic fairy tale, supported by critical thinking questions and a glossary of key physics terms"